The Routledge international handbook of learning with technology in early childhood - Kucirkova, Natalia; Rowsell, Jennifer 1969-; Falloon, Garry (Routledge, 2019)
"This book brings together innovative work happening in childhood research across disciplinary boundaries and across the world. It focuses specifically on the most cutting-edge, innovative methodological approaches in the study of children's use and learning with digital technologies and children's experiences of key 21st century trends (e.g. immigration or multiculturalism). A true effort is made to have dialogues across diverse fields and contested fields of research (including educational psychology, post-humanist literacy, narrative approaches, developmental approaches). The volume is a substantive and strategic collection of international approaches to early childhood and technologies"--
Description based on print version record
Keywords: Early childhood education / Computer-assisted instruction; Computers and children; Educational technology